The Importance of Murabaha in Long-Term Finance Programs in the Islamic Banking Industry (American Journal of Islam and Society, 1999)
Since the start of the Islamic banking industry many questions have been raised about Islamic finance policies used by Islamic banks and lheir long-term finance programs. The most interesting questions on Islamic finance policies are lhose related to murabaha finance. The argumenl concerning murabaha has two sides, one for and the other against. The questions normally are concentrated on whether Islamic banks should use murabaha in their finance, and whether Islamic banks heavily depend on it in their finance. The aim of this article is to examine the importance of murabaha compared to other Islamic finance policies in long-term finance programs in the Islamic banking industry. The article suggests that musharaka and mudaraba are as important as murabaha in financing long-term programs in the Islamic banking industry.